DIALOGUE OF CULTURE AS A BASIS FOR HUMAN DEVELOPMENT (ON THE BASIS OF PHILOSOPHY OF THE COSMISM) - Пода, T. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
In the article the author shows the universal nature of the ideas of cosmicism and analyzes the possibility of their application for solving modern problems of mankind. It was revealed that the set of ideological questions offered by cosmists, their relevance and significance for modern society gives grounds to define this direction as a perspective global ideology capable of giving the leading ideas, to show new ways of solving modern ecological, ethical, axiological problems.